Stakeholder Analysis in Tourism Development Bintan Regency During the Pandemic COVID-19 - Mahadiansar, Mahadiansar; Wijaya, Andy Fefta; Wanto, Alfi Haris (Journal of Governance and Public Policy, 2021)
In improving the welfare of the people in border areas, the development of the tourism sector has an impact on long-term economic growth which has been the largest regional income source in Bintan Regency. The importance of interaction and stakeholder actors involved in tourism activities during the COVID-19 pandemic. The purpose of this study is to analyze the condition of stakeholder actors in tourism management in Bintan Regency. The research method used a qualitative approach with stakeholder analysis using NVivo 12 with data collection techniques in the form of interviews with stakeholders and using existing secondary data which was carried out in-depth analysis. The results showed that 3 components (who, when, and how) showed a significant correlation between stakeholders in tourism development in Bintan Regency, namely the local government which regulates the executive management as a facilitator. Then the involvement of community groups as active participation to support the development of travel bubble-based tourism in the border region of the country, then the involvement of the private sector who maintain and regulate health protocols in the spread of COVID-19. Furthermore, the alternative is to improve stakeholder relations in the future to make efforts to approach harmonious communication between stakeholders in the tourism sector in Bintan Regency.